The Many Traditions of Liberal Arts—and Their Global Relevance - Altbach, Philip G (International Higher Education, 2016)
Liberal education has many traditions, including some which are non-Western. This article discusses Confucian, India, and other liberal arts antecedents in the context of the contemporary interest in liberal arts globally.